(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Considerazioni introduttive - 2. La provenienza dei magistrati dall’Università - 3. La conoscenza del diritto canonico - 4. La nomina pontificia - 5. La stabilità delle funzioni - 6. La provenienza nazionale - 7. Annotazioni conclusive. The independence of the Vatican justice. Notes on the magistrates of the Court ABSTRACT: Among the judicial organs of the Vatican City State, the Court is the one that has undergone the greatest transformations and the most consistent processes of adaptation to the emerging needs in the juridical experience. The essay illustrates the methods through which the objective was pursued to ensure the independence of the magistrates in charge: at the same time a necessary requirement for the right process and a good thing to protect in a particular way considering the peculiar state reality.